2020
DOI: 10.1038/s41598-020-62386-0
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Silicon Dioxide in Tablet form (Carbowhite) Efficacy in Patients with Acute Diarrhea: Results of Randomized, Double-Blind, Placebo-Controlled, Multi-Center Study

Abstract: the acute diarrhea is a wide-spread disease. the prescription of enterosorbents is appropriate as a primary measure for the treatment of the acute diarrhea for effective prevention of the fluid and electrolyte loss, as well as method for symptom relief of the attack of the disease. Aim of the study -the antidiarrheal efficacy and safety study of high-dispersion silicon dioxide enterosorbent in tablet dosage form in patients with acute diarrhea. This was randomized, double-blind, placebo-controlled, 4-center st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 48 publications
0
10
0
3
Order By: Relevance
“…In contrast, several probiotics and their metabolites may depress the proliferation of pathogenic bacteria, and increase the intestinal barrier function [ 12 , 13 ]. Previous research using administration of colloidal silicon dioxide in tablet form in patients with acute diarrhea revealed that the high-dispersion silicon dioxide enterosorbent exhibited antidiarrheal effect [ 14 ]. Moreover, it is reported that silicon dioxide blocks the receptors of mucous membrane that is responsible for pathogens adhesion and toxins binding, and accelerates the adsorption of active substances in intestine [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several probiotics and their metabolites may depress the proliferation of pathogenic bacteria, and increase the intestinal barrier function [ 12 , 13 ]. Previous research using administration of colloidal silicon dioxide in tablet form in patients with acute diarrhea revealed that the high-dispersion silicon dioxide enterosorbent exhibited antidiarrheal effect [ 14 ]. Moreover, it is reported that silicon dioxide blocks the receptors of mucous membrane that is responsible for pathogens adhesion and toxins binding, and accelerates the adsorption of active substances in intestine [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most adverse events were mild and were gastrointestinal in origin Mesoporous silica ( Bukara et al, 2016 ) (500 nm ( Jammaer et al, 2009 )) Open-label, randomized, two-way cross-over Enhanced delivery of fenofibrate using mesoporous silica compared to micronized fenofibrate Route: Oral No serious adverse events reported and no relevant differences in clinical laboratory tests between the subjects in the treatment and the reference groups Porous silica-lipid nanoparticles ( Tan et al, 2014 ) (15.20 μm with 3–20 nm pores) Randomized, double-blinded, one-period single oral dose (Phase I) Enhanced delivery of ibuprofen using silica to improve solubility compared to commercial tablet Route: Oral Negligible acute side effects related to the administration of both the investigational and reference formulations. Colloidal silica ( Tieroshyn et al, 2020 ) (Size NR) Randomized, double-blind, placebo-controlled, 4-center (Phase II) Silica as an anti-diarrheal agent compared to placebo Route: Oral “Carbowhite” Carbowhite was well tolerated and no adverse effects were reported Silica Shells ( van Zuuren et al, 2021 ) (Size NR) Multi-centered randomized, double blind, vehicle controlled parallel group (Phase II) – Recently FDA Approved ( Randles-Friedman, Iwaniuk ) Prolonged release of benzoyl peroxide using silica shells Route: Topical 52-week long-term safety study, side effects mostly mild Silicic acid anhydride ( Zschocke et al, 2008 ) (Size NR) Randomized, open‐label, comparator‐controlled Comparison of silica vs Topical acyclovir for the treatment of recurrent herpes labialis Route: Topical No serious adverse events …”
Section: Safety Of Silica Nanoparticles In Humanmentioning
confidence: 99%
“…Ця властивість лежить в основі його застосування для видалення екзотоксинів, ендотоксинів, а також для фіксування мікроорганізмів, міцел, ліпопротеїдів. Завдяки наявності на поверхні мікроорганізмів різноманітних білкових структур, високодисперсний діоксид кремнію активно сорбує патогенну мікрофлору (до 10 10 мікробних тіл на 1 грам речовини) та виводить її з кишечника, а це забезпечує виражений протимікробний ефект [13,16].…”
Section: вступunclassified
“…Експериментальні дослідження показали, що високодисперсний діоксид кремнію має також виражені антидіарейні властивості, що пояснюється блокуванням дії стимуляторів секреції рідини в кишечнику (дезоксихолатів натрію, цАМФ і серотоніну) шляхом впливу на відповідні рецептори та вираженими гідрофільними властивостями діоксиду кремнію, що забезпечує структурування кишкового вмісту [13,15].…”
Section: вступunclassified
See 1 more Smart Citation